2017
DOI: 10.1111/echo.13573
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac involvements in hypereosinophilia‐associated syndrome: Case reports and a little review of the literature

Abstract: Hypereosinophilia-associated syndrome is a rare group of systemic diseases without certain underlying causes. Hypereosinophilic syndrome (HES) and eosinophilic granulomatosis with polyangiitis (EGPA), formerly known as Churg-Strauss syndrome (CSS), are initial considerations, when underlying causes remains unexplained despite of complete evaluation of hypereosinophilia. In this study, we report two rare cases, one case of HES with Loeffler endocarditis, and the other one of EGPA with restrictive cardiomyopathy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 11 publications
1
12
0
3
Order By: Relevance
“…Endocardial involvement in patients with EGPA is similar to that of other hypereosinophilic syndromes (idiopathic hypereosinophilic syndrome and its variants, tropical endomyocardial fibrosis) 17–23. The pathological lesion most commonly associated with hypereosinophilic syndromes is referred to as Loeffler’s endocarditis 17–23. Loeffler’s endocarditis occurs less commonly with EGPA than with other hypereosinophilic syndromes 16–22.…”
Section: Discussionmentioning
confidence: 93%
“…Endocardial involvement in patients with EGPA is similar to that of other hypereosinophilic syndromes (idiopathic hypereosinophilic syndrome and its variants, tropical endomyocardial fibrosis) 17–23. The pathological lesion most commonly associated with hypereosinophilic syndromes is referred to as Loeffler’s endocarditis 17–23. Loeffler’s endocarditis occurs less commonly with EGPA than with other hypereosinophilic syndromes 16–22.…”
Section: Discussionmentioning
confidence: 93%
“…Although the pathogenesis of hypereosinophilia in our patient remains unclear, it has been reported that the heart is one of the frequently involved organs in cases of eosinophilia . Cardiac involvement is common, and it was first described as eosinophilic endocarditis associated with hypereosinophilia .…”
mentioning
confidence: 78%
“…Cardiac involvement occurs in up to 62% of EGPA cases and it is more common in ANCA‐negative patients with higher blood eosinophil count . Generally, EGPA manifests as vasculitic lesions in the myocardium and the coronary vessels, causing myocarditis (31%), heart failure (21%), pericarditis (21%), atrioventricular blocks (8%), and myocardial infarction (5%) . As for valvular involvement, mitral insufficiency is most commonly described.…”
Section: Review Of the Literature And Discussionmentioning
confidence: 99%
“…13 Generally, EGPA manifests as vasculitic lesions in the myocardium and the coronary vessels, causing myocarditis (31%), heart failure (21%), pericarditis (21%), atrioventricular blocks (8%), and myocardial infarction (5%). 14…”
Section: Re Vie W Of the Liter Ature And Discussionmentioning
confidence: 99%